Clinical benefits of oral anticoagulants in atrial fibrillation patients with dementia: a systematic review and meta-analysis - Wang, Dayang; Xu, Xiaoqing; Han, Xiaowan; Xie, Jing; Zhou, Hufang; Peng, Wenhua; Pan, Guozhong (Frontiers in Cardiovascular Medicine, 2023)
The management of atrial fibrillation (AF) with oral anticoagulants (OAC) is generally recommended to reduce the risk of stroke. However, the decision to prescribe these medications for patients with AF and dementia remains controversial.A systematic review and meta-analysis of retrospective cohort studies were conducted. The search encompassed PubMed, Cochrane Library, Web of Science, and Embase databases from inception until May 1st, 2023, with language limited to English. Eligible studies included comparisons between exposure to OAC vs. non-OAC in the AF population with dementia or cognitive impairment. Studies that compared the effects of noveldirect oral anticoagulants (DNOAC) and vitamin-K antagonists were also included. The primary outcome was all-cause mortality, and the secondary outcomes were ischemic stroke and major bleeding. This study was registered with PROSPERO (No. CRD42023420678).Results: A total of five studies (N=21962 patients) met the eligibility criteria and were included in this review. The follow-up duration ranged from 1 to 4 years. Meta-analysis demonstrated that OAC treatment was associated with a lower risk of all-cause mortality in AF patients with dementia with a hazard ratio (HR) of 0.79 and a 95% confidence interval (CI) ranging from 0.68 to 0.92, (HR 0.79, 95% CI: 0.68-0.92) compared to non-OAC treatment. No statistical differences were observed in the risk of major bleeding (HR 1.12, 95% CI: 0.88-1.42) or ischemic stroke (HR = 0.77, 95% CI: 0.58-1.00). Three studies reported comparisons between DNOAC and warfarin; however, pooled analysis was not performed due to heterogeneity. This is a provisional file, not the final typeset articleThe use of OACs in individuals diagnosed with both AF and dementia holds the potential to reduce all-cause mortality rates, thereby improving the overall clinical prognosis within this specific population.